Job Characteristics, Job-Related Stress and Intention to Stay in Professional Nursing in a Tertiary Care Hospital, Ministry of Public Health - Muneerat, Sawitree; Suwannapong, Nawarat; Tipayamongkholgul, Mathuros; Manmee, Charuwan (Journal of Health Science of Thailand, 2019)
The shortage of nursing personnel, including the problems of leave nursing career and transfers of professional nurses, remains a serious concern in the realm of public health. This cross-sectional research is aimed assessing the intention to stay in professional nursing in Rajavithi hospital. The sample to assess was composed of 360 professional nurses who had worked at the hospital for at least 6 months. From May to July, 2017, a questionnaire was used to collect data for the purpose of assessing their intention to stay in professional nursing. The response rate was 82.8%. Data was analyzed using descriptive statistics and multivariable logistic regression analysis. The resulting Cronbrach’s alpha coefficients were: 0.872 for the intention to stay, 0.901 for job characteristics, and 0.787 for job-related stress. The findings revealed that the professional nurses’ average age was 38.53 years old, the lowest age was 22 years old and the highest age was 59 years old. Their median work experience was 16 years. Regarding the intention to stay in the profession, 72.8% were uncertain, 14.1% had no intention, and 13.1% intended to stay in professional nursing. Overall job characteristics were at a good level (68.1%); job-related stress was at a moderate level (82.2%) and at a high level (17.8%). When considering each aspect, the professional nurses had job-related stress regarding career issues at a high level (62.1%). The factors related to the intention to stay in professional nursing were an age of over 40 years old (Adj. OR=5.738; 95%CI=2.479-13.284), and the perception of job characteristics regarding autonomy at a good level (Adj. OR=3.463; 95%CI=1.625-7.381). Recommendations from research findings : Hospital executives should set policies in promoting autonomy by providing the professional nurses with greater opportunities in their scope of work, and by allowing young professional nurse to plan, to promote their professional advancement, to evaluate work outcome suitable to work assignments, to be able to retain them as long as possible.